Behavior in organizations : understanding and managing the human side of work - Greenberg, Jerald (Pearson Education, 2003)
nformation about human beings and their behaviour is presented in this volume for the benefit of future managers. It includes issues such as how to motivate people, how to give them feedback on their performance and how to influence them